Brain macro- and microscopic damage in patients with paediatric MS. Issue 12 (26th July 2010) - Absinta, Martina; Rocca, Maria A; Moiola, Lucia; Ghezzi, Angelo; Milani, Nicoletta; Veggiotti, Pierangelo; Comi, Giancarlo; Filippi, Massimo
Abstract : Objective: To characterise, using conventional and diffusion tensor (DT) MRI, the nature and distribution of lesions and the extent of damage in the brain normal-appearing white matter (NAWM) and grey matter (GM) from a relatively large population of paediatric multiple sclerosis (MS) patients. Methods: Brain conventional and DT MRI scans were acquired from 48 patients with paediatric MS (10 clinically isolated syndromes (CIS), 38 relapsing remitting (RR) MS), 30 adult CIS, 27 adult RRMS, 15 paediatric healthy controls (HC) and 18 adult HC. T2-lesion probability maps and DT MRI of lesions, NAWM and GM were compared among controls and MS groups. Results: T2-visible lesion volumes did not differ among patient groups, but T2 lesions were more frequently located in the posterior periventricular regions in adult RRMS patients than in adult CIS and paediatric RRMS patients. Adult RRMS patients had a significantly higher lesion average mean diffusivity than paediatric RRMS patients. No DT MRI changes in the NA tissues were found in paediatric and adult CIS patients. DT MRI abnormalities were limited to the NAWM in paediatric RRMS patients, while they involved the NAWM and GM in adult RRMS patients. The extent of NAWM involvement was similar between adult and paediatric RRMS patients and was significantly correlated with T2-visible lesion burden. Conclusions: A less severe intrinsic lesion damage, a less frequent lesion occurrence in the posterior periventricular WM and the sparing of GM may help to explain the favourable short-/medium-term disease outcome of paediatric MS.